Possible ways of IP Commercialisation in the European Higher Education Ecosystem - Peredy, Zoltán; Laki, Balázs (International Journal of Engineering and Management Sciences, 2020)
Strong links between universities, and companies can play crucial role in promoting taking into practice of ideas that drive the knowledge society, and in raising competitiveness and living standards. In academic terms of IP management, all activities aimed at sharing knowledge generated in research institutions as a knowledge transfer including scientific publishing, conference presentations, collaborative research with external partners, and contract-based clustering activities, such as licensing and spin-offs. In a narrower sense, the IP management means technology transfer is aimed at placing a given technology on the market, and includes any process by which the recovery partner becomes able to produce new products or services. IP with traditional university mission, values, and activities primarily focusing an active university role in entrepreneurship and contracts with private sector for IP commercialization. This paper gives a comprehensive overview about IP management in universities of the European Higher Education System including the following aspects: partnerships (licensing, industry collaborators); IP invention (disclosures, patenting); proof of concept research bridging the gap between lab discoveries and market application (highly innovative R&D to solve practical problems and commercialization research aiming patented technologies towards business exploitations) and commercialization (start-up incubators and strengthening the entrepreneurial attitudes and competencies). The methodology based on secondary research analysing EU, OECD, on-line literature sources and relevant, up-to date statistical data as well. The conclusions and recommendations based on this „desk research” work reflects the authors.